Inkjet ink, method for forming cured product, and cured product
The active energy ray curing inkjet ink formulation, featuring a combination of polymerizable compounds, inorganic particles, and hydrophobic silica particles, addresses the challenge of sedimented inorganic particle redispersibility, ensuring stable ejection and extended component durability.
Patent Information
- Application Number
- JP2023163742
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-09-26
AI Technical Summary
Existing active energy ray curing inkjet inks face challenges with the redispersibility of sedimented inorganic particles, leading to unstable ejection and reduced durability of inkjet head components.
The development of an active energy ray curing inkjet ink formulation that includes a polymerizable compound, inorganic particles, and hydrophobic silica particles with an average particle size smaller than the median diameter of the inorganic particles, enhancing redispersibility and preventing aggregation.
The inkjet ink achieves excellent redispersibility of sedimented inorganic particles, maintaining stable ejection and extending the durability of inkjet head components, while also improving the weather resistance of the cured product.
Smart Images

Figure 2025054614000001 
Figure 2025054614000002 
Figure 2025054614000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an ink-jet ink, a method for forming a cured product, and the cured product. [Background technology]
[0002] Inkjet inks containing inorganic particles such as titanium oxide as a white pigment and conductive particles are known. The inorganic particles tend to settle in the ink during storage or while waiting before ejection, and once settled, they are difficult to redisperse.
[0003] To solve this problem, in the ink composition for inkjet recording described in Patent Document 1, silica particles having silanol groups on the surface are used in combination with an inorganic pigment in a water-based ink containing water and an organic solvent as the solvent.
[0004] In addition, in the actinic radiation-curable inkjet ink described in Patent Document 2, which also contains silica particles, silica particles whose surfaces are modified with a (meth)acrylate compound are used in order to suppress sedimentation due to aggregation of the silica particles. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-181055 A [Patent Document 2] JP 2019-157062 A Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 describes that silica particles can facilitate redispersion of precipitated inorganic pigments. However, according to the findings of the present inventors, in an active energy ray-curable inkjet ink containing a polymerizable compound, even if the same silica particles as those in Patent Document 1 are used, the precipitated inorganic pigments are not easily redispersed. Moreover, even if silica particles whose surfaces are modified with a (meth)acrylate compound as described in Patent Document 2 are used, the precipitated inorganic pigments are not easily redispersed in the active energy ray-curable inkjet ink.
[0007] According to another finding by the present inventors, in the case of an active energy ray-curable inkjet ink to which silica particles similar to those in Patent Documents 1 and 2 have been added, problems arise in that the ink is easily deflected when ejected from the inkjet head and the durability of components such as the inkjet head and flow path is easily reduced.
[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an actinic energy ray-curable inkjet ink which has excellent re-dispersibility of settled inorganic particles and is less likely to cause deflection when ejected from an inkjet head or a decrease in the durability of components such as an inkjet head and a flow path, a method for forming a cured product using the inkjet ink, and a cured product formed by the method. [Means for solving the problem]
[0009] One aspect of the present invention for solving the above problems relates to an actinic ray-curable ink-jet ink according to the following items [1] to
[10] . [1] A composition comprising a polymerizable compound, inorganic particles, and silica particles, the silica particles have been subjected to a hydrophobic treatment and have no polymerizable group; the average particle size of the silica particles is smaller than the median particle size of the inorganic particles, The content of the silica particles by mass is less than the content of the inorganic particles by mass; Active energy ray curable inkjet ink. [2] The polymerizable compound contains a (meth)acrylate. [1] The inkjet ink according to the present invention. [3] The (meth)acrylate contains a monofunctional polymerizable compound having an aromatic ring. [2] The inkjet ink according to the present invention. [4] Substantially free of water and substantially free of organic solvents; The ink-jet ink according to any one of [1] to [3]. [5] The average particle size of the silica particles is 1 / 20 or less of the median size of the inorganic particles. The ink-jet ink according to any one of [1] to [4]. [6] The content of the silica particles is 0.01% by mass or more and 5% by mass or less based on the total mass of the inkjet ink. The inkjet ink according to any one of [1] to [5]. [7] The average particle size of the inorganic particles is 0.5 μm or more and 5 μm or less. The inkjet ink according to any one of [1] to [6]. [8] D of the inorganic particles 50 / D 90 is between 0.1 and 0.9, The inkjet ink according to any one of [1] to [7]. [9] The inorganic particles are phosphorescent pigments. The inkjet ink according to any one of [1] to [8].
[10] Including a heat curing agent; The inkjet ink according to any one of [1] to [9].
[0010] Another aspect of the present invention for solving the above problems relates to a method for forming a cured product as described in
[11] to
[12] below.
[11] A step of applying the inkjet ink according to any one of [1] to
[10] to a substrate; irradiating the applied ink-jet ink with active energy rays; The method for forming a cured product comprising the steps of:
[12] The step of applying the ink-jet ink to the substrate is carried out while circulating the ink-jet ink. The method for forming a cured product according to
[11] .
[0011] Another aspect of the present invention for solving the above problems relates to a cured product as described below in
[13] .
[13] A cured product formed from the ink-jet ink according to any one of [1] to
[10] . Effect of the Invention
[0012] According to the present invention, there are provided an active energy ray-curable inkjet ink which has excellent re-dispersibility of settled inorganic particles and is less likely to cause deflection when ejected from an inkjet head or a decrease in durability of components such as an inkjet head or a flow path; a method for forming a cured product using the inkjet ink; and a cured product formed by the method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] 1. Inkjet ink One embodiment of the present invention relates to an active energy ray-curable inkjet ink (hereinafter, simply referred to as "ink") that contains a polymerizable compound, inorganic particles, and hydrophobically treated silica particles.
[0014] In the ink according to the present embodiment, it is believed that silica particles, which are smaller than inorganic pigment particles, are adsorbed to the surface of the inorganic pigment. By adsorbing to the surface of the inorganic pigment, the silica particles suppress packing of the settled inorganic particles and aggregation of the inorganic particles. It is believed that this makes it easier for the silica particles to redisperse the settled inorganic particles.
[0015] The ink according to the present embodiment is an active energy ray curable ink containing a polymerizable compound. The hydrophobized silica particles contained in the ink are easily wetted by the polymerizable compound, which is a liquid component. Therefore, the silica particles are well dispersed in the ink according to the present embodiment. Since the well dispersed silica is well adsorbed to the inorganic particles, it is considered that the ink according to the present embodiment is easy to redisperse the precipitated inorganic particles. The silica particles described in Patent Document 1 are hydrophilized. Such silica particles do not have good wettability to the polymerizable compound. Therefore, it is considered that the silica particles described in Patent Document 1 are difficult to adsorb to the inorganic particles, and it is difficult to increase the redispersibility of the precipitated inorganic particles.
[0016] Moreover, the ink according to this embodiment contains silica particles that do not have a polymerizable group. In the silica particles whose surfaces are modified with a (meth)acrylate compound described in Patent Document 2, the (meth)acryloyl groups on the surfaces undergo a polymerization reaction during storage or flow of the ink, or when the ink is heated inside the inkjet head. The silica particles tend to aggregate with each other due to this polymerization reaction, and are easily detached from the surfaces of the inorganic particles. For this reason, it is believed that the silica particles have difficulty in increasing the redispersibility of the settled inorganic particles.
[0017] If the settled inorganic particles cannot be redispersed, the concentration of the inorganic particles in the ejected inkjet ink is likely to fluctuate, or the viscosity of the inkjet ink may fluctuate, making the ejection unstable. In addition, when the inkjet ink before ejection is circulated in the ink flow path or the inkjet head, the circulation of the inkjet ink is likely to become unstable. In this embodiment, the silica particles make it easier to redisperse the settled inorganic particles, making these problems less likely to occur.
[0018] In addition, inorganic particles usually have high hardness. Inorganic particles with high hardness aggregated in the ink may contact the components of the inkjet head or the ink flow path and deteriorate these components. Furthermore, the aggregated inorganic particles may stick to the nozzle surface and peel off the water-repellent film on the nozzle plate ejection surface, or scrape and deform the nozzle opening, causing ink ejection bending or ejection failure. In contrast, in this embodiment, silica particles that are well wetted with the polymerizable compound are well adsorbed to the inorganic particles, suppressing the aggregation of the inorganic particles. In addition, the silica particles used in this embodiment are unlikely to detach from the surface of the inorganic pigment even when the ink is heated inside the inkjet head during storage or flow, and are unlikely to cause the aggregation of the inorganic particles. Therefore, the ink related to this embodiment is unlikely to reduce the durability of components such as the inkjet head and the ejection property of the ink.
[0019] Each component will be described below.
[0020] 1-1. Polymerizable compounds The polymerizable compound is a compound that undergoes polymerization and crosslinking upon irradiation with active energy rays.
[0021] The polymerizable compound can be a monomer, an oligomer, a polymer, and mixtures thereof.
[0022] The polymerizable compound may be a monofunctional compound or a polyfunctional compound. When it is desired to make the cured product flexible, it is preferable to include a monofunctional compound, and when it is desired to increase the hardness of the cured product, it is preferable to include a multifunctional compound. In addition, from the viewpoint of balancing these, the polymerizable compound may include both a monofunctional compound and a polyfunctional compound.
[0023] The polymerizable compound may be a radically polymerizable compound or a cationic polymerizable compound, and the polymerizable compound may be a combination of a radically polymerizable compound and a cationic polymerizable compound.
[0024] The radically polymerizable compound is a compound having an ethylenically unsaturated bond capable of radical polymerization.
[0025] Examples of the compound having a radically polymerizable ethylenically unsaturated bond include unsaturated carboxylic acids and their salts, unsaturated carboxylic acid ester compounds, unsaturated carboxylic acid urethane compounds, unsaturated carboxylic acid amide compounds and their anhydrides, acrylonitrile, styrene, unsaturated polyesters, unsaturated polyethers, unsaturated polyamides, and unsaturated urethanes, etc. Examples of unsaturated carboxylic acids include (meth)acrylic acid, itaconic acid, crotonic acid, isocrotonic acid, maleic acid, etc.
[0026] Among them, the radical polymerizable compound is preferably an unsaturated carboxylic acid ester compound, and more preferably a (meth)acrylate. Since the (meth)acrylate itself has high thermal stability, it can also increase the thermal stability of the ink. Therefore, the ink containing the (meth)acrylate has high thermal stability inside the inkjet head, and is less likely to cause ejection bending. The (meth)acrylate may be a monomer or an oligomer, which will be described later, or may be a mixture of a monomer and an oligomer, a modified product, an oligomer having a polymerizable functional group, or the like.
[0027] In this specification, (meth)acrylate refers to acrylate or methacrylate, (meth)acryloyl refers to acryloyl or methacryloyl, and (meth)acrylic refers to acrylic or methacrylic.
[0028] Examples of monofunctional (meth)acrylates include isoamyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, isomylstyryl (meth)acrylate, isostearyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 2-ethylhexyl-diglycol (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-(meth)acryloyloxyethylhexahydrophthalic acid, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenol (meth)acrylate, m-phenoxybenzyl (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, ethoxylated phenoxy (meth)acrylate, alkoxylated phenol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-o-phenylphenolpropyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl-phthalate, and t-butylcyclohexyl (meth)acrylate.
[0029] Examples of polyfunctional (meth)acrylates include triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol diacrylate, dimethylol-tricyclodecane di(meth)acrylate, bisphenol A type di(meth)acrylate, and hydroxypivalin. Examples of the (meth)acrylates include difunctional (meth)acrylates such as acid neopentyl glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, and tripropylene glycol diacrylate, as well as trifunctional or higher (meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, glycerin propoxy tri(meth)acrylate, and pentaerythritol ethoxy tetra(meth)acrylate.
[0030] The (meth)acrylate may be a modified product. Examples of modified (meth)acrylates include ethylene oxide modified (meth)acrylates including ethylene oxide modified trimethylolpropane tri(meth)acrylate and ethylene oxide modified pentaerythritol tetraacrylate, caprolactone modified (meth)acrylates including caprolactone modified trimethylolpropane tri(meth)acrylate, and caprolactam modified (meth)acrylates including caprolactam modified dipentaerythritol hexa(meth)acrylate.
[0031] The (meth)acrylate may be a polymerizable oligomer. Examples of the (meth)acrylate that is a polymerizable oligomer include an epoxy (meth)acrylate oligomer, an aliphatic urethane (meth)acrylate oligomer, an aromatic urethane (meth)acrylate oligomer, a polyester (meth)acrylate oligomer, and a linear (meth)acrylic oligomer.
[0032] Examples of the cationically polymerizable compound include an epoxy compound, a vinyl ether compound, and an oxetane compound.
[0033] Examples of epoxy compounds include 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, bis(3,4-epoxycyclohexylmethyl)adipate, vinylcyclohexene monoepoxide, ε-caprolactone-modified 3,4-epoxycyclohexylmethyl 3',4'-epoxycyclohexanecarboxylate, alicyclic epoxy resins such as 1-methyl-4-(2-methyloxiranyl)-7-oxabicyclo[4,1,0]heptane, 2-(3,4-epoxycyclohexyl-5,5-spiro-3,4-epoxy)cyclohexanone-meta-dioxane and bis(2,3-epoxycyclopentyl)ether, diglycidyl ether of neopentyl glycol, diglycidyl ether of 1,4-butanediol, diglycidyl ether of 1,6-hexanediol, triglycidyl ether of glycerin, triglycidyl ether of trimethylolpropane, diglycidyl ether of ethylene glycol, and the like. Examples of the epoxy compounds include aliphatic epoxy compounds including polyglycidyl ethers of polyether polyols obtained by adding one or more alkylene oxides (such as ethylene oxide and propylene oxide) to aliphatic polyhydric alcohols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, and glycerin, as well as di- or polyglycidyl ethers of bisphenol A or its alkylene oxide adducts, di- or polyglycidyl ethers of hydrogenated bisphenol A or its alkylene oxide adducts, and novolac-type epoxy resins.
[0034] Examples of the vinyl ether compound include monovinyl ether compounds including ethyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, octadecyl vinyl ether, cyclohexyl vinyl ether, hydroxybutyl vinyl ether, 2-ethylhexyl vinyl ether, cyclohexanedimethanol monovinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, isopropenyl ether-o-propylene carbonate, dodecyl vinyl ether, diethylene glycol monovinyl ether, and octadecyl vinyl ether, as well as di- or trivinyl ether compounds including ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, propylene glycol divinyl ether, dipropylene glycol divinyl ether, butanediol divinyl ether, hexanediol divinyl ether, cyclohexanedimethanol divinyl ether, and trimethylolpropane trivinyl ether.
[0035] Examples of the oxetane compound include 3-hydroxymethyl-3-methyloxetane, 3-hydroxymethyl-3-ethyloxetane, 3-hydroxymethyl-3-propyloxetane, 3-hydroxymethyl-3-n-butyloxetane, 3-hydroxymethyl-3-phenyloxetane, 3-hydroxymethyl-3-benzyloxetane, 3-hydroxyethyl-3-methyloxetane, 3-hydroxyethyl-3-ethyloxetane, 3-hydroxyethyl-3-propyloxetane, 3-hydroxyethyl-3-phenyloxetane, 3-hydroxyethyl-3-phenyloxetane, These include 3-hydroxypropyl-3-methyloxetane, 3-hydroxypropyl-3-ethyloxetane, 3-hydroxypropyl-3-propyloxetane, 3-hydroxypropyl-3-phenyloxetane, 3-hydroxybutyl-3-methyloxetane, 3,3'-(oxybismethylene)bis(3-ethyloxetane), 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and di[1-ethyl(3-oxetanyl)]methyl ether.
[0036] The polymerizable compound preferably contains a compound having an aromatic ring in the molecule. Aromatic rings are structurally stable and therefore are less susceptible to hydrogen abstraction. Therefore, polymerizable compounds having aromatic rings in the molecule are less susceptible to yellowing of the cured product due to hydrogen abstraction reactions caused by a large amount of radicals generated during curing of the ink. In addition, the compound having an aromatic ring in the molecule is preferably a monofunctional polymerizable compound. Polymerizable compounds having aromatic rings at the terminals have high wettability to inorganic particles, making it easier to redisperse precipitated inorganic particles.
[0037] The content of the polymerizable compound having an aromatic ring is preferably from 10% by mass to 80% by mass, and more preferably from 20% by mass to 70% by mass, based on the total mass of the ink.
[0038] Examples of the polymerizable compound having an aromatic ring include phenol 4EO modified (meth)acrylate, 2-phenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenol (meth)acrylate, m-phenoxybenzyl (meth)acrylate, alkoxylated phenol (meth)acrylate, 2-hydroxy-o-phenylphenolpropyl (meth)acrylate, EO modified o-phenylphenol (meth)acrylate, bisphenol fluorene di (meth)acrylate (A-BPEF), bisphenol A type 10EO modified di(meth)acrylate, bisphenol A type di(meth)acrylate, bisphenol A type PO modified di(meth)acrylate, bisphenol A type EO modified di(meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate. Of these, phenol 4EO-modified (meth)acrylate, 2-phenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenol (meth)acrylate, m-phenoxybenzyl (meth)acrylate, alkoxylated phenol (meth)acrylate, 2-hydroxy-o-phenylphenolpropyl (meth)acrylate, EO-modified o-phenylphenol (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate are preferred.
[0039] The content of the polymerizable compound is preferably from 30% to 97% by mass, and more preferably from 60% to 95% by mass, based on the total mass of the ink. The content of the monofunctional polymerizable compound having an aromatic ring is preferably from 10% to 60% by mass, and more preferably from 20% to 50% by mass, based on the total mass of the ink.
[0040] 1-2.Inorganic particles The type of inorganic particles is not particularly limited. The inorganic particles may be pigment particles that impart characteristics such as color tone, electrical conductivity, insulating properties, heat dissipation properties, and a negative thermal expansion coefficient to a cured product formed from the ink, or may be particles that are added separately from the pigment to adjust the physical properties of the cured product.
[0041] The inorganic particles may be particles containing atoms other than carbon as a main component, where "containing atoms other than carbon" means that 50 mass % or more of the total mass of the inorganic particles is an atom other than carbon.
[0042] Examples of inorganic particles include: Silica particles, Metal oxide particles such as titanium oxide particles, alumina particles, zirconia particles, zinc oxide particles, and iron oxide particles Metal hydroxide particles, such as magnesium hydroxide particles, aluminum hydroxide particles, and calcium hydroxide particles Nitride particles such as silicon nitride particles, titanium nitride particles, and aluminum nitride particles Luster pigment particles such as silver particles (or conductive particles), Glass particles such as glass beads and glass flakes; silicate particles, such as magnesium silicate particles; Kaolin particles, calcined kaolin particles, ceramic particles such as clay, talc, and zeolite, Particles made of composite materials such as pearl pigment particles, Luminous pigment particles that can absorb light of a specific wavelength, store the light energy, and release the stored light energy for a long period of time as light of a different wavelength than the absorbed light. etc.
[0043] Examples of phosphorescent pigments include those in which the host crystal of a metal compound has been subjected to an activation treatment.
[0044] Examples of the above-mentioned parent crystal include sulfides such as zinc sulfide, calcium sulfide, germanium sulfide, strontium sulfide, and yttrium sulfide, metal oxides such as calcium oxide, strontium oxide, barium oxide, alumina, and cerium oxide, and aluminates such as calcium aluminate, strontium aluminate, and barium aluminate, etc. Of these, strontium aluminate (SrAl2O4:Eu,Dy) is preferred.
[0045] Examples of the activator for activating the mother crystal include europium, terbium, yttrium, zirconium, dysprosium, barium, etc. Among these, europium and dysprosium are preferred.
[0046] The peak wavelength of the excitation spectrum of the phosphorescent pigment is preferably 300 nm or more and 400 nm or less. When the peak wavelength of the excitation spectrum of the phosphorescent pigment is in the above range, the phosphorescent pigment can be sufficiently excited by sunlight, and the cured product can be easily adapted for outdoor use.
[0047] The peak wavelength of the emission spectrum of the phosphorescent pigment may be, for example, from 400 nm to 700 nm, and from the viewpoint of further improving the visibility of the cured product, it is preferably from 450 nm to 600 nm.
[0048] Among these inorganic particles, glittering pigment particles, zinc oxide particles, and phosphorescent pigment particles are preferred. Furthermore, since silica particles are easily adsorbed and easily improve redispersibility after settling, zinc oxide particles, pearl pigment particles, and phosphorescent pigment particles are more preferred, and phosphorescent pigment particles are even more preferred.
[0049] The shape of the inorganic particles is not particularly limited, and may be spherical or non-spherical such as flat plate or whisker. Among these, spherical is preferred because it is easy to enhance the effect of improving redispersibility after settling by silica particles. For example, the aspect ratio of the inorganic particles, which is the ratio of the major axis to the minor axis, is preferably 1.0 to 1.5, more preferably 1.0 to 1.2.
[0050] The long axis and short axis of the inorganic particles can be the average of the long axis and the average of the short axis in an image of 1,000 inorganic particles arbitrarily selected from the inorganic particles in the ink captured in an image taken with a transmission electron microscope (TEM) or a scanning electron microscope (SEM), respectively.
[0051] The median diameter of the inorganic particles in the ink is not particularly limited, and can be 0.2 μm or more and 20 μm or less, preferably 0.3 μm or more and 10 μm or less, more preferably 0.5 μm or more and 5 μm or less, and even more preferably 1.0 μm or more and 5 μm or less. The larger the median diameter, the easier it is to increase the amount of silica particles adsorbed to the inorganic particles, and the easier it is to increase the redispersibility after settling by the silica particles. In addition, the larger the median diameter, the harder it is for the settled inorganic particles to pack and the easier it is to redisperse. The smaller the median diameter, the better the ejection from the inkjet head, and even if they aggregate, the less likely they are to damage components such as the inkjet head.
[0052] The median diameter of inorganic particles is the particle size at which the cumulative value in the volume-based particle size distribution is 50% (D 50 ) can be used.
[0053] The particle size at which the cumulative value of the volume-based particle size distribution of inorganic particles in the ink is 90% (D 90 ) can be 1.0 μm or more and 20 μm or less, preferably 1.5 μm or more and 10 μm or less, and more preferably 2.0 μm or more and 8 μm or less. It is easy to increase the amount of silica particles adsorbed to the inorganic particles, and it is easy to increase the redispersibility after sedimentation by the silica particles. In addition, D 90 The larger the D, the less likely the precipitated inorganic particles are to be packed together and the easier they are to be redispersed. 90 The smaller the diameter, the better the ejection properties from the inkjet head, and even if the ink aggregates, it is less likely to damage components such as the inkjet head.
[0054] In addition, inorganic particles are 50 / D90 is preferably 0.2 or more and 0.8 or less, and more preferably 0.3 or more and 0.6 or less. 50 / D 90 The smaller the t, the broader the particle size distribution can be, and the more densely packed the inorganic particles can be in a cured product, which can improve the weather resistance of the cured product.
[0055] In addition, the D of inorganic particles 50 and D. 90 can be a value measured using a particle size measuring device, for example, LUMiSizer, manufactured by LUM Japan Co., Ltd.
[0056] The specific gravity of the inorganic particles can be from 2 to 6, preferably from 2.5 to 5, and more preferably from 3 to 4.5. The larger the specific gravity, the easier the inorganic particles will settle in the ink, and the silica particles will have a significant effect of improving redispersibility after settling.
[0057] The inorganic particles may be dispersed by a dispersant. The inorganic particles may be dispersed by only one type of dispersant, or may be dispersed by two or more types of dispersants.
[0058] Examples of dispersants include carboxylates having a hydroxyl group, salts of long-chain polyaminoamides and high molecular weight acid esters, salts of high molecular weight polycarboxylic acids, salts of long-chain polyaminoamides and polar acid esters, high molecular weight unsaturated acid esters, polymer copolymers, modified polyurethanes, modified polyacrylates, polyether ester-type anionic surfactants, naphthalenesulfonic acid formalin condensate salts, aromatic sulfonic acid formalin condensate salts, polyoxyethylene alkyl phosphate esters, polyoxyethylene nonylphenyl ether, and stearylamine acetate. Commercially available examples of pigment dispersants include the Solsperse series (manufactured by Avecia, "Solsperse" is a registered trademark of the company), the PB series (manufactured by Ajinomoto Fine-Techno Co., Ltd.), and the EFKA series (manufactured by BASF, "EFKA" is a registered trademark of the company).
[0059] The content of the dispersant is preferably 0.01% by mass or more and 20% by mass or less with respect to the total mass of the inorganic particles.
[0060] The content of inorganic particles may be set according to the application of the inorganic particles. For example, the content of inorganic particles may be 1% by mass or more and 60% by mass or less, preferably 2% by mass or more and 50% by mass or less, and more preferably 3% by mass or more and 30% by mass or less, based on the total mass of the ink. The lower the content of inorganic particles, the higher the redispersibility of the precipitated inorganic particles.
[0061] 1-3.Silica particles Silica particles are particles whose average particle size is smaller than the median size of inorganic particles. Silica particles smaller than inorganic particles are easily adsorbed to the surface of inorganic particles, and are easy to suppress packing and aggregation of inorganic particles. It is considered that this makes it easier for silica particles to redisperse precipitated inorganic particles. For the same reason, it is also considered that silica particles suppress the deterioration of durability of components such as inkjet heads and the ejection properties of ink when ink containing inorganic pigments is used.
[0062] The silica particles may be particles made of silicon dioxide (SiO2), or may be particles containing silicon dioxide as a main component and other substances. The silica particles may also be core-shell type particles containing a core and a shell containing silicon dioxide. Incidentally, containing as a main component means that 50 mass% or more of the total mass of the particles is silicon dioxide. From the viewpoint of increasing the redispersibility and circulation stability of the precipitated inorganic particles, it is preferable that the silica particles are particles made of only silicon dioxide. The silica particles may be natural or synthetic, but synthetic particles are preferable because the average particle size and particle size distribution are easily adjusted.
[0063] The silica particles, which are synthetic products, may be silica particles produced by a dry method or silica particles produced by a wet method. Examples of silica particles produced by a dry method include combustion silica particles produced by a combustion method and deflagration silica particles produced by a deflagration method. Examples of silica particles produced by a wet method include precipitated silica particles produced by a precipitation method, silica gel, colloidal silica, and sol-gel silica produced by a gel method. Among these, combustion silica, deflagration silica, and sol-gel silica are preferred because of their high adsorption to inorganic particles, and sol-gel silica is more preferred.
[0064] The silica particles are hydrophobized. The hydrophobized silica particles are easily wetted by the polymerizable compound and easily disperse in the ink. Therefore, the hydrophobized silica particles are easily adsorbed to the inorganic surface in the ink, and are easy to increase the redispersibility of the precipitated inorganic particles and to suppress the deterioration of the durability and ejection property of the member.
[0065] The method of hydrophobic treatment is not particularly limited, and treatment with a silane coupling agent having a hydrophobic group (such as an alkyl group), a titanium coupling agent having a hydrophobic group (such as an alkyl group), polysiloxane, disilazane, silicone oil, long-chain fatty acid, or the like may be used. The hydrophobic treatment may be carried out using, for example, chlorosilanes including ethyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, diphenyldichlorosilane, t-butyldimethylchlorosilane, and vinyltrichlorosilane, tetramethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, o-methylphenyltrimethoxysilane, p-methylphenyltrimethoxysilane, n-butyltrimethoxysilane, i-butyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, diphenyldiethoxysilane, i-butyltriethoxysilane, decyltriethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-glycid ... alkoxysilanes including propyltrimethoxysilane, gamma-glycidoxypropylmethyldimethoxysilane, gamma-mercaptopropyltrimethoxysilane, gamma-chloropropyltrimethoxysilane, gamma-aminopropyltrimethoxysilane, gamma-aminopropyltriethoxysilane, gamma-(2-aminoethyl)aminopropyltrimethoxysilane, and gamma-(2-aminoethyl)aminopropylmethyldimethoxysilane, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, hexamethylcyclotetrasiloxane, octa ... polysiloxanes including silane, decamethylcyclopentasiloxane, hexamethyldisiloxane, octamethyltrisiloxane, and the like; disilazanes including hexamethyldisilazane, hexaethyldisilazane, hexapropyldisilazane, hexabutyldisilazane, hexapentyldisilazane, hexahexyldisilazane, hexacyclohexyldisilazane, hexaphenyldisilazane, divinyltetramethyldisilazane, and dimethyltetravinyldisilazane, and the like; dimethyl silicone oils;The reaction can be carried out using silicone oils including methylhydrogen silicone oil, methylphenyl silicone oil, alkyl-modified silicone oil, chloroalkyl-modified silicone oil, chlorophenyl-modified silicone oil, fatty acid-modified silicone oil, polyether-modified silicone oil, alkoxy-modified silicone oil, carbinol-modified silicone oil, amino-modified silicone oil, fluorine-modified silicone oil, and terminally reactive silicone oil, as well as long-chain fatty acids such as undecylic acid, lauric acid, tridecylic acid, dodecylic acid, myristic acid, palmitic acid, pentadecylic acid, stearic acid, heptadecylic acid, arachidic acid, montanic acid, oleic acid, linoleic acid, and arachidonic acid, or salts thereof.
[0066] In this specification, the hydrophobic treatment does not include treatment that includes a polymerizable group. Examples of the polymerizable group include an epoxy group, a (meth)acryloyl group, and a vinyl group. Hydroxyl groups and silanol groups do not react with polymerizable compounds, so they are not included in the polymerizable group.
[0067] The hydrophobicity of the hydrophobic treated silica particles is preferably 30% or more and 80% or less, and more preferably 50% or more and 75% or less.
[0068] The hydrophobicity of the silica particles is determined by adding 0.2 mass % of silica particles to 50 ml of ion-exchanged water, dropping methanol from a burette while stirring with a magnetic stirrer, and measuring the mass fraction of methanol in the methanol-water mixed solution at the end point when all of the silica particles have sunk.
[0069] The average particle size of the silica particles is preferably 1 / 2 or less of the median size of the inorganic particles, more preferably 1 / 10 or less, even more preferably 1 / 20 or less, and particularly preferably 1 / 50 or less. The smaller the ratio of the average particle size of the silica particles to the median size of the inorganic particles, the easier it is to adsorb the silica particles to the surface of the inorganic particles. In particular, by making the average particle size of the silica particles 1 / 20 or less of the median size of the inorganic particles, the ratio of the specific surface area of the silica particles to the surface area of the inorganic particles can be increased, and the silica particles can be more easily adsorbed to the surface of the inorganic particles. The lower limit of the ratio of the average particle size of the silica particles to the median size of the inorganic particles is not particularly limited, but it is preferably 1 / 500 or more.
[0070] The average particle size of the silica particles is preferably 0.005 μm or more and 1.5 μm or less, more preferably 0.01 μm or more and 1.0 μm or less, and even more preferably 0.05 μm or more and 0.5 μm or less. The smaller the average particle size of the silica particles, the higher the redispersibility of the settled inorganic particles. By increasing the average particle size of the silica particles to a certain extent, the specific surface area of the inorganic particles to which the silica particles are attached can be reduced, making it difficult for the inorganic particles to scratch the nozzle surface.
[0071] The average particle diameter of silica particles can be the value published by the manufacturer. It can also be measured as the volume average diameter using a particle size measuring device and dynamic light scattering. For example, a slurry containing silica particles is diluted with ion-exchanged water so that the content of silica particles is 0.1% by mass, and the diluted slurry is irradiated with laser light, and the scattered light intensity scattered from the inorganic silica particles is measured in microseconds. The scattering intensity distribution caused by the detected silica particles is fitted to a normal distribution, and the Z-average particle diameter of the silica particles is obtained by cumulant analysis. For example, a Zetasizer Nano ZS manufactured by Spectris can be used as a particle size measuring device. The particle size measuring device is equipped with data analysis software, which automatically analyzes the measurement data to calculate the Z-average particle diameter.
[0072] The shape of silica particles is preferably spherical.For example, the aspect ratio of silica particles, which is the ratio of major axis to minor axis, is preferably 1.0 or more and 1.5 or less, more preferably 1.0 or more and 1.2 or less.The major axis and minor axis of silica particles can be measured in the same manner as the major axis and minor axis of inorganic particles described above.
[0073] The content of silica particles can be 0.01% by mass or more and 5% by mass or less, preferably 0.01% by mass or more and 3% by mass or less, more preferably 0.01% by mass or more and 2% by mass or less, and even more preferably 0.01% by mass or more and 1.5% by mass or less, based on the total mass of the ink. If the content of silica particles is 0.01% by mass or more, the redispersibility of the settled inorganic particles is improved. If the content of silica particles is 5% by mass or less, the decrease in ejection performance due to silica particles not adsorbed to the inorganic particles and damage to components such as the inkjet head are suppressed.
[0074] In addition, the ratio of the silica particle content to the inorganic particle content (silica particle content (by mass) / inorganic particle content (by mass)) is preferably 0.0004 or more and 0.3 or less, more preferably 0.004 or more and 0.2 or less, and even more preferably 0.01 or more and 0.1 or less.
[0075] 1-3.Other ingredients The ink may further contain other ingredients such as photoinitiators, organic pigments, dyes, thermal curing agents, surfactants, optical brighteners, gelling agents, and polymerization inhibitors.
[0076] The photopolymerization initiator can be a radical initiator when the ink contains a radical polymerizable compound, and a cationic initiator (photoacid generator) when the ink contains a cationic polymerizable compound. When the polymerization is initiated by irradiation with an electron beam, the ink does not need to contain a photopolymerization initiator.
[0077] Examples of the radical polymerization initiator include a hydrogen abstraction type photopolymerization initiator, an intramolecular cleavage type photopolymerization initiator, etc. The hydrogen abstraction type photopolymerization initiator includes an intramolecular hydrogen abstraction type photopolymerization initiator, an intermolecular hydrogen abstraction type photopolymerization initiator, etc.
[0078] The intramolecular hydrogen abstraction type photopolymerization initiator is a photopolymerization initiator that is excited by irradiation with active energy rays and generates a hydrogen abstraction reaction in the molecule to generate radicals. Examples of the intramolecular hydrogen abstraction type photopolymerization initiator include benzoyl formate-based photopolymerization initiators such as methyl phenylglyoxylate, and oxyphenyl-based photopolymerization initiators such as a mixture of oxyphenylacetic acid-2-[2-oxo-2-phenylacetoxy-ethoxy]ethyl ester and oxyphenylacetic acid 2-[2-hydroxy-ethoxy]ethyl ester. Among these, compounds having a glyoxylic acid structure such as benzoyl formate-based photopolymerization initiators are preferred because they are less likely to cause hydrogen abstraction from the molecular chain of the polymerizable compound during polymerization.
[0079] Examples of commercially available intramolecular hydrogen abstraction type photopolymerization initiators include Omnirad MBF and Omnirad 754 (both manufactured by IGM Resins, "Omnirad" being a registered trademark of the company).
[0080] The intermolecular hydrogen abstraction type photopolymerization initiator is a photopolymerization initiator that is excited by irradiation with active energy rays such as ultraviolet rays and abstracts hydrogen from other molecules to generate radicals. Examples of the intermolecular hydrogen abstraction type photopolymerization initiator include benzophenone-based initiators including benzophenone, o-benzoyl methyl benzoate, 4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, and 3,3'-dimethyl-4-methoxybenzophenone, and thioxanthone-based initiators such as 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone.
[0081] Examples of commercially available intermolecular hydrogen abstraction type photopolymerization initiators include Omnirad 500 (manufactured by IGM Resins) and Speedcure ITX (manufactured by Sartomer, "Speedcure" is a registered trademark of Arkema France).
[0082] Examples of the intramolecular cleavage type photopolymerization initiator include acetophenone-based initiators such as 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-2-morpholino(4-methylthiophenyl)propan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone; benzoin-based initiators such as benzoin, benzoin methyl ether, and benzoin isopropyl ether; and acylphosphine oxide-based initiators such as 2,4,6-trimethylbenzoin diphenylphosphine oxide and bis(2,4,6-trimethylbenzoin)phenylphosphine oxide.
[0083] Commercially available examples of intramolecular cleavage type photopolymerization initiators include Omnirad 127, Omnirad 184, Omnirad 651, Omnirad 2959, Omnirad 819, and Esacure One (all manufactured by IGM Resins).
[0084] The content of the photopolymerization initiator is preferably 3% by mass or more and 20% by mass or less, more preferably 3% by mass or more and 15% by mass or less, even more preferably 3% by mass or more and 10% by mass or less, and particularly preferably 5% by mass or more and 10% by mass or less, based on the total mass of the polymerizable material. By making the content 3% by mass or more, the curability and adhesion of the ink can be further improved.
[0085] Examples of organic pigments include red pigments, yellow pigments, blue pigments, white pigments, etc., which are used in inks for forming images. Known pigments can be used for these pigments. Examples of dyes include red dyes, yellow dyes, blue dyes, etc., which are used in inks for forming images. Known dyes can be used for these dyes.
[0086] Examples of the thermal curing agent include polyfunctional epoxy compounds, polyfunctional oxetane compounds, imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole, amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine, phosphine compounds such as tributylphosphine and triphenylphosphine, and adipic acid dihydrazide and sebacic acid dihydrazide. Examples of the acid anhydrides include hydrazine compounds, melamine resins, benzoguanamine resins, melamine derivatives, amino resins such as benzoguanamine derivatives, blocked isocyanate compounds, cyclocarbonate compounds, cyclic (thio)ether compounds, bismaleimides, carbodiimide resins, aromatic amines, reaction products of amine compounds and epoxy compounds, as well as acid anhydrides such as phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, 3-chlorophthalic anhydride, 4-chlorophthalic anhydride, benzophenonetetracarboxylic anhydride, succinic anhydride, methylsuccinic anhydride, dimethylsuccinic anhydride, dichlorosuccinic anhydride, methylnadic acid, dodecylsuccinic anhydride, chlorendec anhydride, and maleic anhydride.
[0087] When a heat curing agent is used, a curing catalyst may be used in combination. Examples of the curing catalyst include imidazole derivatives, guanamines, polyamines, their organic acid salts, epoxy adducts, triazine derivatives, tertiary amines, organic phosphines, phosphonium salts, and quaternary ammonium salts.
[0088] The content of the heat curing agent is not particularly limited, but can be, for example, from 0.1% by mass to 10% by mass relative to the total mass of the ink.
[0089] When the ink contains a heat curing agent, it is preferable that the ink contains, as a polymerizable compound, a compound having a functional group that reacts with the heat curing agent, such as an epoxy group, an oxetane group, or a carboxyl group. On the other hand, even if the polymerizable compound does not contain a functional group that reacts with the heat curing agent, the polymerization of the polymerizable compound can be promoted by the exothermic reaction of the heat curing agent.
[0090] Examples of surfactants include anionic surfactants such as dialkyl sulfosuccinates, alkyl naphthalene sulfonates, and fatty acid salts; nonionic surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkyl allyl ethers, acetylene glycols, and polyoxyethylene-polyoxypropylene block copolymers; cationic surfactants such as alkylamine salts and quaternary ammonium salts; and silicone-based and fluorine-based surfactants.
[0091] The content of the surfactant is not particularly limited, but can be, for example, from 0.001% by mass to less than 1.0% by mass relative to the total mass of the ink.
[0092] The gelling agent is a compound that causes the ink to be in a gel state at room temperature (25°C) and in a sol state when heated (e.g., 80°C). For example, the gelling agent is preferably a compound that dissolves in the liquid components (polymerizable compounds and organic solvents, etc.) contained in the ink at a temperature higher than the gelling temperature of the ink and crystallizes at a temperature lower than the gelling temperature of the ink. The gelling temperature means the temperature at which the ink undergoes a phase transition from sol to gel and the viscosity of the ink suddenly changes when the ink that has been solated or liquefied by heating is cooled. Specifically, the temperature at which the viscosity of the ink suddenly increases when the ink that has been solated or liquefied by heating is cooled while the viscosity is measured with a rheometer (e.g., MCR300, manufactured by Anton Paar) can be regarded as the gelling temperature of the ink.
[0093] Examples of gelling agents include ketone waxes, ester waxes, petroleum waxes, vegetable waxes, animal waxes, mineral waxes, hydrogenated castor oil, modified waxes, higher fatty acids, higher alcohols, hydroxystearic acid, fatty acid amides including N-substituted fatty acid amides and special fatty acid amides, higher amines, esters of sucrose fatty acids, synthetic waxes, dibenzylidene sorbitol, dimer acid and dimer diol.
[0094] The content of the gelling agent is preferably from 1.0% to 10.0% by mass, more preferably from 2.0% to 7.5% by mass, and even more preferably from 2.0% to 3.5% by mass, relative to the total mass of the ink.
[0095] Examples of the polymerization inhibitor include N-oxyl-based polymerization inhibitors, phenol-based polymerization inhibitors, quinone-based polymerization inhibitors, amine-based polymerization inhibitors, copper dithiocarbamate-based polymerization inhibitors, etc. The polymerization inhibitor may be contained in the ink alone or in combination of two or more types.
[0096] Examples of N-oxyl polymerization inhibitors include 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO), 4-hydroxy-2,2,6,6-tetramethyl-piperidine-N-oxyl, 4-oxo-2,2,6,6-tetramethyl-piperidine-N-oxyl, 4-methoxy-2,2,6,6-tetramethyl-piperidine-N-oxyl, 4-acetoxy-2,2,6,6-tetramethyl-piperidine-N-oxyl, etc. Examples of commercially available N-oxyl polymerization inhibitors include Irgastab UV10 (manufactured by BASF ("Irgastab" is a registered trademark of the company)).
[0097] Examples of the phenol-based polymerization inhibitor include 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2-tert-butyl-4,6-dimethylphenol, 2,6-di-tert-butyl-4-methylphenol, 2,4,6-tri-tert-butylphenol, 2,6-di-t-butyl-p-cresol (butylated hydroxytoluene: BHT), 4-methoxyphenol, 2-methoxy-4-methylphenol, and the like.
[0098] Examples of the quinone polymerization inhibitor include hydroquinone, methoxyhydroquinone, benzoquinone, 1,4-naphthoquinone, and p-tert-butylcatechol.
[0099] Examples of amine-based polymerization inhibitors include alkylated diphenylamines, N,N'-diphenyl-p-phenylenediamine, phenothiazine, and the like.
[0100] Examples of the copper dithiocarbamate polymerization inhibitor include copper dimethyldithiocarbamate, copper diethyldithiocarbamate, copper dibutyldithiocarbamate, and the like.
[0101] The content of the polymerization inhibitor is not particularly limited, but can be, for example, from 0.01% by mass to 0.5% by mass relative to the total mass of the ink.
[0102] The ink may contain a solvent other than the polymerizable compound, such as water and an organic solvent.
[0103] Examples of organic solvents include aliphatic alcohols, aromatic alcohols, diols, triols, glycol ethers, poly(glycol) ethers, lactams, formamides, acetamides, long chain alcohols, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, glycerin, dipropylene glycol, glycol butyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, dipropylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol, polypropylene glycol, methyl oleate, methyl caprylate, methyl caprate, and methyl laurate. , methyl myristate, methyl palmitate, methyl stearate, methyl oleate, methyl tallowate, methyl rice bran fatty acid, methyl rapeseed fatty acid, methyl soyate, n-butyl palmitate, n-butyl stearate, n-butyl rapeseed fatty acid, n-butyl soyate, i-butyl rice bran fatty acid, i-butyl rapeseed fatty acid, octyl palmitate, octyl oleate, octyl rapeseed fatty acid, octyl vegetable fatty acid, isopropyl myristate, and isopropyl palmitate amide, amines, ethers, carboxylic acids, esters, organosulfides, organosulfoxides, sulfones, alcohol derivatives, carbitol, butyl carbitol, cellosolves, ether derivatives, amino alcohols and ketones.
[0104] In addition, silica particles are not easily wetted by water. Therefore, water is likely to aggregate silica particles and inhibit the adsorption of silica particles to inorganic particles. From the viewpoint of making silica particles easily adsorbed to inorganic particles, making precipitated inorganic particles easily redispersed, suppressing the deterioration of durability of components such as inkjet heads, and suppressing the deterioration of ink ejection properties, it is preferable that the ink does not substantially contain water.
[0105] In addition, the hydrophobized silica particles are excessively wetted by the organic solvent. Therefore, the organic solvent strongly adheres to the periphery of the silica particles, making it difficult for the silica particles to approach the inorganic particles, and may inhibit the adsorption of silica to the inorganic particles. From the viewpoint of making it easier for the silica particles to be adsorbed to the inorganic particles, making it easier to redisperse the precipitated inorganic particles, suppressing the deterioration of the durability of the members such as the inkjet head, and suppressing the deterioration of the ejection property of the ink, it is preferable that the ink does not substantially contain an organic solvent.
[0106] In this specification, the ink being substantially free of a certain component means that the content of that component relative to the total mass of the ink is 5% by mass or less. From the above viewpoints, the content of water relative to the total mass of the ink is preferably 0% by mass or more and 1% by mass or less, and more preferably 0% by mass or more and 0.1% by mass or less. In addition, the content of organic solvent relative to the total mass of the ink is preferably 0% by mass or more and 1% by mass or less, and more preferably 0% by mass or more and 0.1% by mass or less.
[0107] 1-4. Ink properties The viscosity of the ink is not particularly limited, but the viscosity at 25°C is preferably 5 mPa·s or more and 1000 mPa·s or less, and more preferably 20 mPa·s or more and 500 mPa·s or less. Ink is often stored or on standby at about 25°C. The lower the viscosity at 25°C, the easier it is to redisperse the inorganic pigment that has settled. On the other hand, by appropriately increasing the viscosity at 25°C, it is possible to suppress the settling of the inorganic pigment.
[0108] The viscosity of the composition at 25°C can be determined by a rheometer at a shear rate of 1000 / sec. The rheometer can be a stress-controlled rheometer Physica MCR series manufactured by Anton Paar. The diameter of the cone plate can be 75 mm, and the cone angle can be 1.0°.
[0109] The ink has a volume resistivity of 10 11It is preferable that the cured film can have a resistivity of Ω·m or more. The surface resistivity of the cured film can be measured using a Hiresta UX (MCP-HT800, manufactured by Nitto Seiko Analytech Co., Ltd.).
[0110] 1-5. Ink preparation method The ink can be prepared by mixing the above-mentioned components. In this case, the components other than the inorganic particles may be mixed first, and the inorganic particles may be added to the resulting mixture later.
[0111] In addition, when dispersing inorganic particles with a dispersant, a dispersion liquid containing inorganic particles, a dispersant, and a liquid component may be prepared in advance, and the remaining components may be added and mixed thereto. In this case, in order to increase the solubility of the dispersant, etc., it is preferable to prepare the dispersion liquid by mixing the inorganic particles and the dispersant while heating them.
[0112] In addition, when the inorganic particles are dispersed with a dispersant, the silica particles may be added in advance and dispersed. From the viewpoint of wetting the silica particles with the ink and allowing them to penetrate between the inorganic particles, it is preferable to add the silica particles in advance at the time of dispersion.
[0113] 2. Method for forming the cured product The ink described above can be used to form a cured product by applying it to a substrate by an inkjet method and curing it.
[0114] The application of the ink to the substrate may be performed by ejecting the ink from an inkjet head and allowing the ink to land on the substrate.
[0115] The ejection method from the inkjet head may be either an on-demand method or a continuous method. The on-demand inkjet head may be any of electro-mechanical conversion types such as single cavity type, double cavity type, bender type, piston type, shear mode type, and shared wall type, and electro-thermal conversion types such as thermal inkjet type and bubble jet type ("Bubble Jet" is a registered trademark of Canon Inc.).
[0116] These inkjet heads or image forming apparatuses having inkjet heads may have a configuration in which the ink is circulated inside or outside the inkjet head. When the ink is circulated while being ejected, if inorganic particles settle in the ink circulation flow path, the ejectability of the ink may be reduced. In contrast, in the present embodiment, the redispersibility of the settled inorganic particles is good, so that good ejectability can be maintained even when the ink is circulated.
[0117] The type of the substrate is not particularly limited, and may be, for example, paper, a resin film, an ABS resin plate, an acrylic resin plate, an aluminum plate, a glass plate, a polycarbonate plate, a cloth, etc. The shape of the substrate is not particularly limited, and may be a plate, a film, a sheet, or various three-dimensional shapes. The composition may be applied to the space formed inside the substrate by various methods.
[0118] The ink can be cured by polymerizing and crosslinking the polymerizable compound by irradiation with active energy rays. Examples of active energy rays include electron beams, ultraviolet rays, α rays, γ rays, and X-rays. Of these, ultraviolet rays and electron beams are preferred. The ultraviolet rays are preferably light having a peak wavelength of 360 nm or more and 410 nm or less. The ultraviolet rays are preferably irradiated from an LED light source. LEDs emit less radiant heat than conventional light sources (e.g., metal halide lamps), so when LEDs are used, the ink is less likely to melt when irradiated with active energy rays, and uneven gloss is less likely to occur.
[0119] When ultraviolet rays are used as the active energy rays, the light intensity per irradiation is 500 mJ / cm 2 More than 4000mJ / cm 2 It is preferable that the intensity is 500 mJ / cm or less. 2 When the intensity is 4000 mJ / cm or more, the curability of the polymerizable compound can be improved. 2 When the content is equal to or less than this, discoloration of the cured product can be suppressed.
[0120] When forming a cured product with a large thickness, the application of the ink and the formation of a film may be repeated.
[0121] It is considered that the silica particles adsorbed on the surfaces of the inorganic particles are also adsorbed or attached to the surfaces of the inorganic particles inside the cured product. Therefore, the surfaces of the inorganic particles in the cured product formed in this embodiment are protected by the silica particles, and the cured product has high abrasion resistance.
[0122] After the cured product is produced in this manner, a protective film for covering the cured product may be formed using a varnish, a laminating film, an ink, or the like, or the cured product may be post-processed into a desired shape. EXAMPLES
[0123] The present invention will be specifically described below with reference to examples, but the scope of the present invention is not limited to the description of the examples.
[0124] [Experiment 1] 1. Preparation of materials An inkjet ink was prepared using the following materials:
[0125] 1-1. Polymerizable compounds Monomer 1: Neopentyl glycol diglycidyl ether (difunctional, non-aromatic) Monomer 2: 1,6-Hexanediol diglycidyl ether (difunctional, non-aromatic) Monomer 3: Triethylene glycol divinyl ether (difunctional, non-aromatic) Monomer 4: 3,3'-(oxybismethylene)bis(3-ethyloxetane) (bifunctional, non-aromatic) Acrylate 1: Dipropylene glycol diacrylate (bifunctional, non-aromatic) Acrylate 2: Polyethylene glycol (200) diacrylate (bifunctional, non-aromatic) Acrylate 3: 1,6-Hexanediol diacrylate (bifunctional, non-aromatic) Acrylate 4: Isobornyl acrylate (monofunctional, non-aromatic) Acrylate 5: Cyclic trimethylolpropane formal acrylate (monofunctional, non-aromatic) Acrylate 6: Benzyl acrylate (monofunctional, aromatic) Acrylate 7: Phenol 4EO acrylate (monofunctional, aromatic) Acrylate 8: 2-phenoxyethyl acrylate (monofunctional, aromatic) Acrylate 9: Glycidyl ether group-containing epoxy acrylate oligomer (manufactured by Shin-Nakamura Chemical Co., Ltd., NK Oligo EA-1010N) (multifunctional, aromatic)
[0126] 1-2.Inorganic particles Inorganic particle 1: zinc oxide (Sakai Chemical Industry Co., Ltd., Candy Zinc 1000 ("Candy Zinz" is a registered trademark of the company)) Inorganic particle 2: Barium sulfate (Sakai Chemical Industry Co., Ltd., H-LFM) Inorganic particle 3: pearl pigment (Merck, Iriodin 111 104259 ("Iriodin" is a registered trademark of the company)) Inorganic particle 4: Luminous pigment (manufactured by Nemoto Specialty Chemical Co., Ltd., Luminova G-300F ("Luminova" is a registered trademark of the company) Inorganic particle 5: Luminous pigment (Luminova G-300FF, manufactured by Nemoto Specialty Chemicals Co., Ltd.)
[0127] 1-3.Silica particles Silica 1: Shin-Etsu Chemical Co., Ltd., QSG-170 (average particle size: 170 nm), hydrophobicity 67% Silica 2: Shin-Etsu Chemical Co., Ltd., QSG-130 (average particle size: 130 nm), hydrophobicity 67% Silica 3: Shin-Etsu Chemical Co., Ltd., QSG-30 (average particle size: 30 nm), hydrophobicity 67% Silica 4: Shin-Etsu Chemical Co., Ltd., QSG-10 (average particle size: 10 nm), hydrophobicity 67% Silica 5: Reolosil MT-10 (average particle size: 15 nm) manufactured by Tokuyama Corporation (Reolosil is a registered trademark of the company) Silica 6: Tokuyama Corporation, Reolosil DM-10 (average particle size: 15 nm) Silica 7: Tokuyama Corporation, Reolosil HM-20L (average particle size: 12 nm) Silica 8: Tokuyama Corporation, Reolosil ZD-30ST (average particle size: 7 nm) Silica 9: Silfil NHM-3N, manufactured by Tokuyama Corporation (average particle size: 150 nm, "Silfil" is a registered trademark of the company) Silica 10: Sunseal SP-01MS (average particle size: 100 nm) manufactured by Tokuyama Corporation (Sunseal is a registered trademark of the company) Silica 11: Sunseal SP-01P (average particle size: 100 nm), manufactured by Tokuyama Corporation Silica 12: Sunseal SP-04MS (average particle size: 400 nm), manufactured by Tokuyama Corporation Silica 13: Sunseal SP-03P (average particle size: 300 nm), manufactured by Tokuyama Corporation Silica 14: Sunseal SP-10M (average particle size: 1000 nm), manufactured by Tokuyama Corporation Silica 15: Tokuyama Corporation, Sunseal SP-10P (average particle size: 1000 nm) Silica 16: Tokuyama Corporation, Reolosil QS-09 (average particle size: 20 nm) Silica 17: Tokuyama Corporation, Silfil NSS-3N (average particle size: 150 nm) Silica 18: Tokuyama Corporation, Sunseal SS-03 (average particle size: 300 nm) Silica 19: Admatechs Co., Ltd., SC2300-SVJ (average particle size: 500 nm) Silica 20: Admatechs Co., Ltd., SC2500-SMJ (average particle size: 500 nm) Silica 21: Nissan Chemical Co., Ltd., PGM-AC-4130Y (average particle size: 45 nm) Silica 22: MEK-AC-4130Y (average particle size: 45 nm), manufactured by Nissan Chemical Co., Ltd.
[0128] Incidentally, silica 1 to silica 15 are silica particles that have been hydrophobized and do not contain a polymerizable group. Silica 16 to silica 18 are silica particles that have not been hydrophobized and are therefore hydrophilic and do not contain a polymerizable group. Silica 19 is a silica particle that has been hydrophobized and contains a vinyl group that is a polymerizable group. Silica 20 is a silica particle that has been hydrophobized and contains a methacryloyl group that is a polymerizable group. Silica 21 is a silica particle that has been hydrophobized and contains an acryloyl group that is a polymerizable group. Silica 22 is a silica particle that has been hydrophobized and contains an acryloyl group that is a polymerizable group.
[0129] 1-4. Photopolymerization initiator Initiator 1: Omnirad MBF, manufactured by IGM RESINS BV Initiator 2: Omnirad 754, manufactured by IGM RESINS BV Initiator 3: Omnirad 819, manufactured by IGM RESINS BV
[0130] 1-5.Heat curing agent Heat Curing Agent 1: Dicyandiamide Heat curing agent 2: LANXESS blocked isocyanate BI7982 Heat hardener 3: 2-ethyl-4-methylimidazole
[0131] 1-6. Organic solvents Organic solvent 1: Methyl oleate Organic solvent 2: Methyl ethyl ketone
[0132] 1-7.Other ingredients Polymerization inhibitor: BASF, Irgastab UV-10
[0133] 2. Inkjet Ink Preparation 2-1. Preparation of dispersion 20 parts by mass of inorganic particles 1 and 80 parts by mass of monomer 1 were placed in a polypropylene container together with 50 parts by mass of zirconia beads having an average particle size of 0.3 mm, and a dispersion treatment was carried out for 30 minutes using a paint shaker. The zirconia beads were then removed to prepare dispersion 1A-1.
[0134] 20 parts by mass of inorganic particles 1 and 80 parts by mass of monomer 2 were placed in a polypropylene container together with 50 parts by mass of zirconia beads having an average particle size of 0.3 mm, and a dispersion treatment was carried out for 30 minutes using a paint shaker. The zirconia beads were then removed to prepare dispersion 1A-2.
[0135] 20 parts by weight of inorganic particles 1 and 80 parts by weight of acrylate 1 were placed in a polypropylene container together with 50 parts by weight of zirconia beads having an average particle size of 0.3 mm, and a dispersion treatment was carried out for 30 minutes using a paint shaker. The zirconia beads were then removed to prepare dispersion 1A-3.
[0136] Dispersion liquid 1B was prepared in the same manner as in the preparation of dispersion liquid 1A-3, except that the dispersion time was changed to 2 hours.
[0137] Dispersion liquid 1C to Dispersion liquid 1F were prepared in the same manner as Dispersion liquid 1A-3, except that inorganic particles were changed to Inorganic Particles 2 to 5, respectively.
[0138] Dispersion liquid 1G was prepared in the same manner as in the preparation of dispersion liquid 1F, except that the dispersion time was changed to 8 hours.
[0139] Dispersion liquid 1H was prepared in the same manner as in the preparation of dispersion liquid 1F, except that the dispersion time was changed to 10 hours.
[0140] Dispersion liquid 1I was prepared in the same manner as in the preparation of dispersion liquid 1F, except that the dispersion time was changed to 16 hours.
[0141] Thereafter, the median diameter of the inorganic particles in the dispersion was measured using a particle size distribution analyzer (LUMiSizer, manufactured by LUM Japan Co., Ltd.) that utilizes the Stokes sedimentation method.
[0142] 2-2. Preparation of ink The polymerizable compound, dispersion, silica particles, photopolymerization initiator, heat curing agent, organic solvent, water, and polymerization inhibitor were mixed in the ratios shown in Tables 1 to 10 and filtered through a 30 μm polypropylene pleated filter (manufactured by ROKI TECHNO Co., Ltd.) to obtain inks 1 to 65. The numerical values shown in parentheses in the columns "inorganic particles" and "silica particles" in Tables 1 to 10 are the median diameter and average particle diameter of each particle in the dispersion.
[0143] [Table 1]
[0144] [Table 2]
[0145] [Table 3]
[0146] [Table 4]
[0147] [Table 5]
[0148] [Table 6]
[0149] [Table 7]
[0150] [Table 8]
[0151] [Table 9]
[0152] [Table 10]
[0153] 3. Evaluation The inks 1 to 65 prepared above were evaluated as follows.
[0154] 3-1. Settling recovery 10 g of the sample was placed in a 20 mL glass sample tube and left to stand at 25°C for 3 days to allow the solid matter to accumulate at the bottom of the sample tube. The sediment was shaken up and down vigorously by hand to measure the number of shakes required to loosen the sediment. A After 1 to 10 times, most of the deposits will come off from the bottom of the sample tube. B After 11 to 30 times, the sediment is almost completely peeled off from the bottom of the sample tube. C. Does not come off from the bottom of the sediment sample tube within 31 tries.
[0155] 3-2.Injection bending The ink was filled into a Konica Minolta independently driven inkjet head (360 npi, discharge volume 27 pL, 1024 nozzles) and a continuous discharge test was carried out for 10 minutes using a strobe-synchronized droplet observation device. After that, the ink was evaluated for ejection deflection according to the following criteria. (standard) A: Of the 256 nozzles evaluated, all 256 nozzles were ejecting normally. B: Of the 256 nozzles evaluated, 1 or more but less than 5 nozzles were observed to have deflected ejection. C: Of the 256 nozzles evaluated, 5 or more nozzles were observed to have deflected nozzle ejection.
[0156] 3-3. Durability of components A maintenance cloth (Savina CK: manufactured by KB Seiren) with each ink attached was pressed against the nozzle face of a Konica Minolta KM1024iLHE and rubbed 100 times, after which the surface of the nozzle face was observed. A: Almost no scratches B: Slightly scratched C: Large scratches are visible
[0157] 3-4.Yellowing Ink 1 to Ink 65 were applied to a 160 mm × 160 mm, 2 mm thick ABS board substrate, and cured with a UV LED curing lamp (Phoseon FireJet FJ100) at a wavelength of 365 nm and an illuminance of 2 W / cm. 2 , light intensity 2000mJ / cm 2 The resulting cured products were left to stand in a 60°C thermostatic chamber for 5 days, after which the appearance of the cured products was observed as follows. A: Almost no change was observed after the test compared to before the test. B: The color of the cured film has changed slightly compared to before the test.
[0158] 3-5. Weather resistance Ink 1 to Ink 65 were applied to a 160 mm × 160 mm, 2 mm thick ABS board substrate, and cured with a UV LED curing lamp (Phoseon FireJet FJ100) at a wavelength of 365 nm and an illuminance of 2 W / cm. 2 , light intensity 2000mJ / cm 2 Each cured product was then irradiated with ultraviolet light of 255 W / m2 in the wavelength range of 300 nm to 700 nm inclusive, and cured to a thickness of 300 microns. A weather resistance test was performed on each cured product in accordance with JIS B 7753:2007. Specifically, the substrate having each cured product was subjected to a weather resistance test using a Sunshine carbon arc lamp accelerated weather resistance tester (Sunshine Weather Meter S80, manufactured by Suga Test Instruments Co., Ltd.) at an irradiance of 255 W / m2 in the wavelength range of 300 nm to 700 nm inclusive. 2 The experiment consisted of 102 minutes of exposure to light and 18 minutes of water spraying for 78 hours. 〇 Almost no color change was observed in the cured film after the test compared to before the test. △: The color of the cured film changed slightly after the test compared to before the test.
[0159] The evaluation results of each ink are shown in Tables 11 to 20. The numerical values shown in the "Silica diameter / inorganic particle diameter" column in Tables 11 to 20 indicate the ratio of the average particle diameter of the silica particles to the median diameter of the inorganic particles used in each ink, with "A" indicating 1 / 20 or less, "B" indicating greater than 1 / 20 and less than 1 / 1, and "C" indicating 1 / 1 or more.
[0160] [Table 11]
[0161] [Table 12]
[0162] [Table 13]
[0163] [Table 14]
[0164] [Table 15]
[0165] [Table 16]
[0166] [Table 17]
[0167] [Table 18]
[0168] [Table 19]
[0169] [Table 20]
[0170] As is clear from the results of Tables 1 to 20, the active energy ray curable inkjet ink, which contains a polymerizable compound, inorganic particles, and silica particles that have been hydrophobized and have no polymerizable groups, and in which the average particle size of the silica particles is smaller than the median size of the inorganic particles and the content of the silica particles by mass is smaller than the content of the inorganic particles by mass, was excellent in redispersibility of settled inorganic particles. Furthermore, although the inkjet ink contains an inorganic pigment, it was unlikely to cause a decrease in durability of components such as an inkjet head or a decrease in ink ejection properties.
[0171] [Experiment 2] Inorganic particles D 50 and D. 90 In order to confirm the difference in sedimentation recovery due to the difference in the sedimentation recovery rate, the following experiment was carried out. In the following description, the explanation of the contents common to Experiment 1 will be omitted, and the explanation of the differences from Experiment 1 will be described. Also, the materials used and their abbreviations are the same as those in Experiment 1, so the explanation will be omitted.
[0172] 1. Inkjet Ink Preparation 1-1. Preparation of dispersion 50 parts by mass of inorganic particles 4 and 50 parts by mass of acrylate 1 were placed in a polypropylene container together with 100 parts by mass of zirconia beads having an average particle size of 0.3 mm, and a dispersion treatment was carried out for 30 minutes using a paint shaker. The zirconia beads were then removed to prepare dispersion liquid 2A.
[0173] Dispersion liquid 2B was prepared in the same manner as in the preparation of dispersion liquid 2A, except that inorganic particles were changed to inorganic particles 5.
[0174] Dispersion liquid 2C was prepared in the same manner as in the preparation of dispersion liquid 2B, except that the dispersion time was changed to 8 hours.
[0175] 1-2. Preparation of ink The polymerizable compound, dispersion, silica particles, photopolymerization initiator, heat curing agent, organic solvent, water, and polymerization inhibitor were mixed in the ratios shown in Table 21 and filtered through a 30 μm polypropylene pleated filter (manufactured by ROKI TECHNO Co., Ltd.) to obtain inks 66 to 73. The values in parentheses in the "Inorganic particles" and "Silica particles" columns in Table 21 are the median diameter and average particle diameter of each particle in the dispersion.
[0176] In addition, Ink 66 to Ink 73 were diluted with dipropylene glycol diacrylate, and the D of inorganic particles contained in each ink was measured using a particle size distribution analyzer (LUMiSizer, manufactured by LUM Japan Co., Ltd.). 50 and D. 90 The measured D 50 , D 90 and D. 50 / D 90 are also shown in Table 21.
[0177] [Table 21]
[0178] For Inks 66 to 73, the same evaluation as in Experiment 1 was carried out. The results are shown in Table 22.
[0179] [Table 22]
[0180] As is clear from the results in Tables 21 and 22, the D 90 The larger the D, the higher the settling return of inorganic particles. 50 / D 90 The smaller the value, the higher the weather resistance of the cured product. [Industrial Applicability]
[0181] According to the present invention, it is possible to make it easier to use ink-jet inks containing inorganic particles. Therefore, the present invention is expected to broaden the applications to which ink-jet inks can be applied and contribute to further development of this field.
Claims
1. The composition comprises a polymerizable compound, inorganic particles, and silica particles, the silica particles have been subjected to a hydrophobic treatment and have no polymerizable group; the average particle size of the silica particles is smaller than the median particle size of the inorganic particles, The content of the silica particles by mass is less than the content of the inorganic particles by mass; Active energy ray curable inkjet ink.
2. The polymerizable compound includes a (meth)acrylate. The ink-jet ink of claim 1.
3. The (meth)acrylate contains a monofunctional polymerizable compound having an aromatic ring. The ink-jet ink of claim 2.
4. Contains substantially no water and substantially no organic solvent; The ink-jet ink of claim 1.
5. The average particle size of the silica particles is 1 / 20 or less of the median size of the inorganic particles. The ink-jet ink of claim 1.
6. the content of the silica particles is 0.01% by mass or more and 5% by mass or less with respect to the total mass of the inkjet ink; The ink-jet ink of claim 1.
7. The average particle size of the inorganic particles is 0.5 μm or more and 5 μm or less. The ink-jet ink of claim 1.
8. D of the inorganic particles 50 / D 90 is equal to or greater than 0.1 and equal to or less than 0.9, The ink-jet ink of claim 1.
9. The inorganic particles are phosphorescent pigments. The ink-jet ink of claim 1.
10. Contains a heat curing agent, The ink-jet ink of claim 1.
11. applying the inkjet ink of any one of claims 1 to 10 to a substrate; irradiating the applied ink-jet ink with active energy rays; The method for forming a cured product comprising the steps of:
12. The step of applying the ink-jet ink to the substrate is performed while circulating the ink-jet ink. A method for forming a cured product according to claim 11.
13. A cured product formed from the ink-jet ink according to any one of claims 1 to 10.
Citation Information
Patent Citations
Ultraviolet curable coating material composition and method for manufacturing laminated product by using the same
JP2001207086A
Marking method and ink
JP2007238400A
Ultraviolet light-emitting diode-curable ink
JP2012162646A
Method of forming non-electric power display object
JP2014028484A
Coating material, printing material and coat material
JP2014166698A